Kompetensi Pedagogik Guru Abad 21 : Tinjauan Peran Guru Menghadapi Generasi Alpha - Ofita, Cherly; Sururi, S (Jurnal Tata Kelola Pendidikan, 2023)
The development of the times means that human education and thinking continues to change and develop dynamically. This article aims to determine the importance of 21st century teacher pedagogy in facing the Alpha generation. The gap in the learning process in the classroom occurs because teachers and students have different learning periods, so the pedagogical competence of teachers in the 21st century and the characteristics of the Alpha generation are important to understand. This study method is a literature study by examining 15 scientific articles published in various national journals and analyzed according to the pedagogical study theme. The problem that often occurs is the gap in the delivery of teaching material in the classroom due to the teacher's lack of understanding of the characteristics of students. Students have now entered the Alpha generation, where the characteristics of students are very different from those of teachers, so teachers need to improve their pedagogical abilities and competencies by knowing the characteristics of the Alpha generation. It is hoped that the results of this study will allow teachers to develop pedagogical competence, especially in dealing with the Alpha generation, so that learning in the classroom occurs optimally and educational goals can be achieved